2021
DOI: 10.3390/land10020202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Previous Crop Roots on Soil Compaction in 2 Yr Rotations under a No-Tillage System

Abstract: Compacted soils affect global crop productivity and environmental quality. A field study was conducted from 2014 to 2020 in the northern Great Plains, USA, to evaluate the effect of various rooting systems on soil compaction in 2 yr rotations of camelina (Camelina sativa L.), carinata (Brassica carinata A.) and a cover crop mix planted in place of fallow with durum (Triticum durum D.). The study was designed as a randomized complete block with three replications in a no-tillage system. The soil was classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Although not quantified, the root systems for both pea and wheat tended to be less developed with thinner and have less deep roots under compaction, as demonstrated in other studies ( Unger and Kaspar, 1994 ). Using plant rooting activity to restore compacted soils is a well-accepted approach, but not all crops are suitable for this because of their thin and shallow roots ( Drewry, 2006 ; Jabro et al, 2021 ). Additionally, such an approach typically requires more than one growing season as the natural recovery process can take decades ( Drewry, 2006 ; Jabro et al, 2021 ) when compared to mechanical loosening through, for example, deep ripping or disking ( Nawaz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not quantified, the root systems for both pea and wheat tended to be less developed with thinner and have less deep roots under compaction, as demonstrated in other studies ( Unger and Kaspar, 1994 ). Using plant rooting activity to restore compacted soils is a well-accepted approach, but not all crops are suitable for this because of their thin and shallow roots ( Drewry, 2006 ; Jabro et al, 2021 ). Additionally, such an approach typically requires more than one growing season as the natural recovery process can take decades ( Drewry, 2006 ; Jabro et al, 2021 ) when compared to mechanical loosening through, for example, deep ripping or disking ( Nawaz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using plant rooting activity to restore compacted soils is a well-accepted approach, but not all crops are suitable for this because of their thin and shallow roots ( Drewry, 2006 ; Jabro et al, 2021 ). Additionally, such an approach typically requires more than one growing season as the natural recovery process can take decades ( Drewry, 2006 ; Jabro et al, 2021 ) when compared to mechanical loosening through, for example, deep ripping or disking ( Nawaz et al, 2013 ). Furthermore, recovery is largely dependent on the physical and mineralogical constitution of the soil ( Schjønning et al, 2015 ), but here, we tested only one type of soil and we can therefore not assess the influence of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the effects of compaction in a clayey soil can be mitigated over time as a function of biopores formed by predecessor crops, especially cover crops, combined with the natural wetting and drying cycles of the soil [71]. Similarly, in a sandy loam soil, the use of cover crops reduced soil resistance to penetration by 25% compared to the value of 2 MPa after two crop rotation cycles, and 32% after three cycles [72]. These authors also verified that plant roots need approximately 4 to 6 years to decompose and produce biopores through the compacted soil layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still a need for further studies to validate those values already identified or to present new values. In addition, crops have different responses to soil limitations; soil bulk density is dependent on soil texture [19] and penetration resistance varies according to soil moisture, bulk density, and texture [38,[67][68][69] according to the three-dimensional variability of the soil and the presence of biopores in compacted soil layers [13,[70][71][72] that enable root growth. All these variables make it difficult to define critical or limiting values for plants, but they should be pursued.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in no-till agricultural land, the use of heavy farming equipment for planting and harvest compacts soil, and recovery may take decades [26][27][28][29]. Soil compaction reduces porosity and limits water and oxygen availability for plant roots, but it also inhibits root growth and the movement of soil organisms [29][30][31][32]. Fertilization application also alters soil nutrient cycling [33] and promotes chemical leaching into waterways that can affect nearby areas [34].…”
Section: Introductionmentioning
confidence: 99%